Effects of macroeconomic uncertainty in China on China-Malaysia bilateral trade - Murodoc, Dilshod Nurillokhanovich (2015)
This study attempts to examine the effects of macroeconomic uncertainty in China due to Chinese industrial production index (IPI) volatility on the conditional variations of China - Malaysia bilateral trade flows. Besides, causality-in-variance analysis is also applied between the volatility of Chinese IPI growth series and the variations of China - Malaysia bilateral trade flows. Obviously, the issue under concern has been the focus of voluminous academic researchers and policy gurus over the past few decades due to its importance in making bilateral trade between countries and policy decisions. Despite the existence of adequate theoretical and empirical studies upon this context, these Asian developing countries have been partially studied due to a limited number of data observations on them for analysis. In that case, this study attempts to redress that imbalance. In model estimation, we exploits monthly time series data for the period from January 1991 to December 2013 and VAR(p)-MGARCH-M-BEKK econometric approach to assess the conditional variance - covariance specification. This is because it is convenient in terms of selection criteria, diagnostic checks in standardized residuals and the variance-non-causality analysis. Based on the model estimation of the study, several important conclusions emerge. First, macroeconomic uncertainty due to Chinese IPI volatility has insignificant impact on the conditional variations of China-Malaysia bilateral trade flows. Besides, causality-in-variance analysis indicates that there are continuously variance transmissions between Chinese IPI growth series and the conditional variations of China-Malaysia bilateral trade flows. By contrast, the variance transmissions from Chinese IPI growth series to the changes of China{Malaysia bilateral trade flows seems to be more prevalent compared to the variance transmissions from the variations of Malaysia's exports to China and Malaysia's imports from China to Chinese IPI growth series. In sum, the results of variance-non-causality analysis show that macroeconomic uncertainty due to Chinese IPI volatility has an explanatory power in determining the future movements of China{Malaysia bilateral trade flows.